2016
DOI: 10.1039/c6ce01631f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth, structures and magnetic properties of copper hydroxide compounds with distorted diamond chain magnetic networks

Abstract: Single crystals of copper hydroxide compounds (1-7) containing organic sulfonate ions (ethane-1,2disulfonate, 1-octanesulfonate, p-toluenesulfonate, p-ethylbenzenesulfonate, 2-naphthalenesulfonate, 1,5naphthalenedisulfonate, and 2,6-naphthalenedisulfonate, respectively) were easily prepared by the hydrolysis of copper acetate aqueous solution containing the respective organic sulfonates. All seven compounds had distorted diamond chain magnetic networks similar to that found in azurite (Cu 3 (CO 3 ) 2 (OH) 2 ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…interactions. The curve presents a sharp maximum at 10.5 K with a very broad shoulder centered around 70 K. This peculiar shape, with two, more or less defined, peaks in  = f(T) has already been observed in other diamond-like Cu(II) hydroxide chains, with sulfonate and acetate ligands, 47 or for the related Cu3(OH)2(CO3)2 azurite. 48 The  = f(T) curve for 1 could be fitted above 7 K, considering isolated chains (separated by the long dodecylsulfate molecules), and the spin topology schematized on figure 8.…”
Section: Comparison With Classical Methods and Morphology Controlsupporting
confidence: 58%
“…interactions. The curve presents a sharp maximum at 10.5 K with a very broad shoulder centered around 70 K. This peculiar shape, with two, more or less defined, peaks in  = f(T) has already been observed in other diamond-like Cu(II) hydroxide chains, with sulfonate and acetate ligands, 47 or for the related Cu3(OH)2(CO3)2 azurite. 48 The  = f(T) curve for 1 could be fitted above 7 K, considering isolated chains (separated by the long dodecylsulfate molecules), and the spin topology schematized on figure 8.…”
Section: Comparison With Classical Methods and Morphology Controlsupporting
confidence: 58%
“…In the present paper we will generalize the localizedmagnon theories established previously for the spin-1/2 Heisenberg diamond and octahedral chains by extending their validity to a less frustrated parameter space including dimer-tetramer [29] and tetramerhexamer [25] ground states, respectively. It is worthwhile to remark that the spin-1/2 Heisenberg diamond chain bears a close relation to several copper-based magnetic compounds such as azurite Cu 3 (CO 3 ) 2 (OH) 2 [30,31], A 3 Cu 3 AlO 2 (SO 4 ) 4 (A = K, Rb, and Cs) [32][33][34], [Cu 3 (OH) 2 (CH 3 COO)(H 2 O) 4 ](RSO 3 ) 2 (RSO 3 = organic sulfonate anions) [35] and Cu 3 (CH 3 COO) 4 (OH) 2 • 5H 2 O [36]. Although we do not have at present any knowledge about a possible experimental realization of the spin-1/2 Heisenberg octahedral chain a relatively numerous family of hexanuclear complexes with the magnetic core of a discrete copper-based octahedron {Cu 6 } [37][38][39][40] could be used for a brick-and-mortar synthesis of a one-dimensional copper polymeric chain of cornersharing octahedra.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, copper hydroxides bearing organic sulfonate ions (RSO 3 − ) were successfully prepared by the hydrolysis of acetate ions, and these compounds were shown to exhibit two-dimensional triangular-lattice or diamond-chain-lattice magnetic networks. 12 In addition, Evrard et al recently reported the successful preparation of single crystals of copper hydroxides with the decanesulfate anion (A = n -C 12 H 25 SO 4 − ) by hydrolysis, and discussed their magnetic properties, among others. 13 The hydrolysis methods are useful for preparation of single crystals of metal hydroxides with various anions and will contribute structural chemistry of them.…”
Section: Introductionmentioning
confidence: 99%